College students’ perception of emojis as linguistic elements in whatsApp messages - Gulo, Yarman Krisman; Harefa, Afore Tahir; Daeli, Hidayati; Zega, Riswan (Cendikia : Media Jurnal Ilmiah Pendidikan, 2025)
In today’s digital era, emojis are widely used in online communication, yet their role remains debated. whether only as decorative symbols or as linguistic elements that convey meaning and shape interpretation. This study investigates college students’ perceptions, usage, and syntactic patterns of emojis in WhatsApp messages Using a descriptive qualitative method with questionnaires, interviews, and digital material from college students in fourth-semester of English Education students at Universitas Nias, the study finds that college students view emojis as meaningful linguistic elements rather than mere decorations. Emojis are used to supplement, replace, or reverse textual meaning, and syntactic analysis identifies four patterns of emojis with sentence: post-text, co-text, pre-text, and pro-text, demonstrating their influence on sentence structure and interpretation The results contribute to understanding emojis as part of linguistic and digital discourse and highlight their relevance to digital literacy and language education.